1991
DOI: 10.1111/j.1365-2265.1991.tb00283.x
|View full text |Cite
|
Sign up to set email alerts
|

High permanent plasma adrenaline levels: a marker of adrenal medullary disease in medullary thyroid carcinoma

Abstract: Increases in urinary, plasma and tumour adrenaline have been previously observed in MEN II patients with phaeochromocytoma. However, the sensitivity of adrenaline for early detection of adrenal medullary disease has not been accurately evaluated. Twenty-five patients with medullary thyroid carcinoma (MTC) histologically confirmed but without clinical or biological evidence of phaeochromocytoma have been studied. Medullary adrenal status was evaluated by adrenal CT-scan. MIBG scintigraphy, determination of urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Since diurnal fluctuations of plasma methoxyamines have, to our knowledge, never been studied, the main goal of this study was to investigate the concentration–time course of plasma methoxyamine levels over the diurnal period in healthy subjects. This work extends our previous findings on the systematic nyctohemeral variations of free plasma catecholamines in patients with multiple endocrine neoplasia type 2A (Vistelle et al. , 1991).…”
supporting
confidence: 89%
“…Since diurnal fluctuations of plasma methoxyamines have, to our knowledge, never been studied, the main goal of this study was to investigate the concentration–time course of plasma methoxyamine levels over the diurnal period in healthy subjects. This work extends our previous findings on the systematic nyctohemeral variations of free plasma catecholamines in patients with multiple endocrine neoplasia type 2A (Vistelle et al. , 1991).…”
supporting
confidence: 89%
“…Total urinary catecholamines (74%) and VMA (71 %) are less reliable (Hamilton et a/., 1978). In some of our recent observations (Vistelle et al, 1991), systematic nycthemeral evaluation of free plasma E and NE showing abnormal elevated nocturnal E favoured the idea that such assays could be valuable in detecting early adrenal medullary disease in MEN 2 A patients. Other methods such as plasma methoxyamines may also be of diagnostic value (Mornex et al, 1991).…”
Section: Surgical and Histological Datamentioning
confidence: 96%
“…However, we have not yet elucidated the mechanism responsible for the upregulation of Epi levels in SPORTS rats. It has been demonstrated that tumors of the adrenal medulla, e.g., pheochromocytoma and neuroblastoma, generate endogenous high levels of Epi (27). In fact, it has been reported that plasma Epi levels in pheochromocytoma patients were over 17-fold higher than after adrenalectomy (28).…”
Section: Articles Integrative Physiologymentioning
confidence: 99%